Methods for construction of generalized moment images of a polynomial kind - Chip , M. M. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Algebraic polynomials that occur in the generalized moment representation of a specified number sequence are found in the form of linear combinations of orthogonal polynomials. The coefficients of these linear combinations are computed from a system of algebraic equations and the polynomials that are found satisfy integral and differential equations.